Anatomical and spiral wave reentry in a simplified model for atrial electrophysiology. (21st April 2017) - Richter, Yvonne; Lind, Pedro G.; Seemann, Gunnar; Maass, Philipp
Abstract: For modeling the propagation of action potentials in the human atria, various models have been developed in the past, which take into account in detail the influence of the numerous ionic currents flowing through the cell membrane. Aiming at a simplified description, the Bueno-Orovio–Cherry–Fenton (BOCF) model for electric wave propagation in the ventricle has been adapted recently to atrial physiology. Here, we study this adapted BOCF (aBOCF) model with respect to its capability to accurately generate spatio-temporal excitation patterns found in anatomical and spiral wave reentry. To this end, we compare results of the aBOCF model with the more detailed one proposed by Courtemanche, Ramirez and Nattel (CRN model). We find that characteristic features of the reentrant excitation patterns seen in the CRN model are well captured by the aBOCF model. This opens the possibility to study origins of atrial fibrillation based on a simplified but still reliable description. Abstract : Graphical abstract: Abstract : Highlights: Modeling of reentry behavior in the human atria with a simple model. Results are comparable to more detailed atrial models. Discussion of merits and limits of the aBOCF model with respect to computational cost, individual-oriented parameter adjustments, analytical treatability, treatment of ionic currents.